Verbal Aggression Behavior in Social Media Interactions: A Literature Review - Gama Dwi Fitrianawati (Kirana Publisher (KNPub), 2026)
The development of social media has significantly changed human communication patterns, but on the other hand, it has given rise to various forms of negative behavior, one of which is verbal aggression. Verbal aggression in social media interactions has become a fairly frequent phenomenon due to the high intensity of use of digital platforms that are fast, anonymous, and have minimal social control. This study aims to comprehensively examine the findings of previous research related to verbal aggression behavior in social media interactions between 2015 and 2025. The method used is a literature study by analyzing 18 scientific articles obtained from various national and international journal databases. The results of this study indicate that verbal aggression on social media is influenced by various factors, including user emotional responses, personality traits, loneliness, fanaticism, socio-political dynamics, and digital media characteristics such as anonymity and discourse polarization. Verbal aggression manifests itself in the form of abusive comments, insults, hate speech, and threats, which negatively impact individual psychological well-being and the quality of online communication. The conclusion of this study confirms that verbal aggression on social media is a multidimensional phenomenon that requires an integrative approach through digital literacy, psychological interventions, policy regulation, and ethical and sustainable technology development.